Strategi Peningkatan Kefasihan Bacaan Al-Qur’an melalui Pendekatan Tajwid Kontekstual di Sekolah Dasar Islam - Wulida Emeris; Tasnim Yawai; Halimatun Hada Wiyah (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This study aims to analyze the effectiveness of the contextual tajwid approach in improving the fluency of Islamic elementary school students in reading the Qur'an. This approach links the rules of tajwid with the real-life contexts of students to create relevant and meaningful learning experiences. The method used is a descriptive qualitative approach with literature study and content analysis techniques. The results of the study indicate that the contextual tajwid strategy, integrated with the Contextual Teaching and Learning (CTL) approach, significantly improves students' understanding, technical skills, and motivation in reading the Qur'an. The role of teachers as facilitators, along with the support of conventional and digital learning media, further strengthens the effectiveness of this approach. Thus, contextual tajwid serves as a strategic alternative in Quranic education that is adaptive to students' needs in the modern era.